THE EFFECTIVENESS OF TONGUE TWISTERS IN IMPROVING JUNIOR HIGH SCHOOL STUDENTS’ PRONUNCIATION: A PRE-EXPERIMENTAL STUDY AT SMP NEGERI 3 - Laluan, Injilia Marchella; Maru, Mister Gidion; Sabudu, Delli (SoCul: International Journal of Research in Social Cultural Issues, 2024)
For many Indonesian learners, mastering English pronunciation is challenging, especially when dealing with unfamiliar sounds, proper stress patterns, and natural rhythm. This study set out to investigate whether Tongue Twisters could be an effective way to address these issues for seventh-grade students at SMP Negeri 3 Tondano. Using a quantitative pre-experimental design with a one-group pre-test and post-test format, the research involved 13 purposively selected students from a BINSUS (Binaan Khusus) class. A pronunciation test adapted from Anas Sudijono’s (2012) rubric measured five aspects: consonants, vowels, stress, intonation, and rhythm, along with tongue twisters. Data were gathered through a pre-test, a single treatment session using Tongue Twisters, and a post-test. The results were analyzed using descriptive statistics, normality testing, and a paired samples t-test in SPSS. Findings showed that the mean score improved from 40.59 in the pre-test to 63.24 in the post-test (scale 0–100). The paired samples t-test confirmed that this improvement was statistically significant (t = -5.592, p < 0.05), indicating that the technique effectively enhanced articulation, vowel accuracy, stress placement, and overall prosody. Beyond measurable progress, students also showed greater engagement and enjoyment during pronunciation practice. These results suggest that incorporating Tongue Twisters into classroom activities can provide both linguistic benefits and a more motivating learning experience for junior high school students.